2018
DOI: 10.3390/geosciences8110418
|View full text |Cite
|
Sign up to set email alerts
|

Rare Biosphere Archaea Assimilate Acetate in Precambrian Terrestrial Subsurface at 2.2 km Depth

Abstract: The deep biosphere contains a large portion of the total microbial communities on Earth, but little is known about the carbon sources that support deep life. In this study, we used Stable Isotope Probing (SIP) and high throughput amplicon sequencing to identify the acetate assimilating microbial communities at 2260 m depth in the bedrock of Outokumpu, Finland. The long-term and short-term effects of acetate on the microbial communities were assessed by DNA-targeted SIP and RNA targeted cell activation. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 83 publications
(166 reference statements)
1
26
0
Order By: Relevance
“…They have been shown to produce nitrous oxide (N 2 O), and host Burkholderia -related endosymbiotic bacteria [ 89 ]. Various types of Burkholderia are common in Outokumpu groundwater, especially in the deeper part of the bedrock [ 50 , 58 ]. Both fungi and Burkholderia could have an advantage due to endosymbiotic relationships, which could help them to adapt to deep subsurface conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been shown to produce nitrous oxide (N 2 O), and host Burkholderia -related endosymbiotic bacteria [ 89 ]. Various types of Burkholderia are common in Outokumpu groundwater, especially in the deeper part of the bedrock [ 50 , 58 ]. Both fungi and Burkholderia could have an advantage due to endosymbiotic relationships, which could help them to adapt to deep subsurface conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acetate is a carbon source for the microorganisms e.g., the chemolithotrophic Dethiobacter [ 96 ]. Similarly, the Outokumpu deep subsurface microbial communities have been shown to use acetate and benefit from acetate during enrichment [ 58 , 61 ]. Here, we showed that Dethiobacter attached to mica schist surfaces especially at 967 m depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rare biosphere, i.e., OTUs comprising less than 1% of the total microbial community, was present in significant extent in both study sites. The rare biosphere represents an important gene pool and may in fact play a disproportionately large role in biogeochemical cycling [92,93]. Interestingly, we could also detect some archaea that usually represent a minor part of the total community in deep subsurface environments, and some fungal signals as well.…”
Section: Microbial Community Structurementioning
confidence: 77%
“…Hence, the microbes of the “rare biosphere” have important roles in the metabolic and ecological functions of aquatic habitats ( 26 28 ). For example, rare archaea are supposed to have ecological functions, such as acetate metabolism ( 29 ), carbon cycling ( 30 ), and methanogenesis ( 31 ). Another interesting component is the taxa which are usually rare but occasionally become more prominent under optimal conditions, namely, the conditionally rare taxa ( 26 , 28 , 32 ).…”
Section: Introductionmentioning
confidence: 99%